Novel Z-Chart for predicting insufficient oil of automotive belt-driven air conditioning compressor - Nuawi, Mohd Zaki; Othman, Muhammad Nur; Ngatiman, Nor Azazi; Yusri, Muhammad Yuszairie (Penerbit Universiti Kebangsaan Malaysia, 2025)
Automotive air conditioning systems play a vital role in ensuring comfort and safety, particularly in tropical climates where high temperatures and humidity demand reliable cooling. The compressor, as the main component, is essential for circulating refrigerant and maintaining system efficiency. Ensuring the compressor operates is crucial as it compromises the performance and could impact the overall functionality of the air conditioning system. The moving components inside the compressor, such as the bearing and piston, require lubrication with a specific quantity of oil. Therefore, maintaining optimal compressor oil levels is crucial to prevent system inefficiencies and potential mechanical failures. This study introduces a novel diagnostic approach using Z-freq 3D statistical analysis to monitor and predict insufficient or excessive oil levels in belt-driven air conditioning compressors. Triaxial vibration data were collected using wireless accelerometers across varying compressor speeds and oil quantities. The data were analyzed and formed into a novel Z-Chart, a control chart that correlates vibration characteristics with oil adequacy. Results reveal that compressors with 80 ml of oil exhibited the lowest vibration, while both insufficient (40 ml, 60 ml) and excessive (100 ml, 120 ml) oil levels led to higher vibration due to suboptimal performance. The Z-Chart, based on the ‘b/a’ coefficient derived from the Gauss Amp model, provides a new visual and quantitative tool for predictive maintenance, enabling early detection of oil-related issues. This method offers significant implications for the automotive industry by reducing operational costs and enhancing compressor reliability. Future research could integrate this technique with IoT-enabled real-time monitoring systems to further improve maintenance practices.